Radiation Risk Analysis of Neuropsychiatric Disorders in Ukrainian Chornobyl Catastrophe Liquidators - Loganovsky, Konstantyn N.; Masiuk, Sergii V.; Buzunov, Vladimir A.; Marazziti, Donatella; Voychulene, Yuliya S. (Frontiers in Psychiatry, 2020)
Goal: To explore the possible impact of ionizing radiation in the pathophysiology of neuropsychiatric disorders amongst clean-up workers of the Chornobyl catastrophe (liquidators). Design, object and methods: Retrospective-prospective study (1987–2015) of liquidators from the State Register of Ukraine (SRU) with radiation doses records and Clinical-Epidemiological Register (CER) of the State Institution «National Research Center for Radiation Medicine of the National Academy of Medical Sciences of Ukraine» (NRCRM). Moreover, cohort and cross-sectional studies of the randomized sample of liquidators from the CER (exposed group, 198 subjects) were examined. Internal control group included the liquidators irradiated in doses <50.0 mSv (42 persons). All subjects were assessed by a detailed clinical examination and a battery of standardized neuropsychiatric scales, psychometric and neuropsychological tests. Descriptive and variation statistics, non-parametric criteria, regression-correlation analysis, survival analysis by Kaplan & Meier, and risk analysis were used. Results: Exposed group vs control group showed cognitive disorders in 99 (50.0%) vs 20 (18.1%), (P=0.04); affective disorders in 96 (48.3%) vs 36 (32.7%) (P=0.007), and stress-related disorders in 115 (58.4%) vs 8 (7.3%) (P<0.001). In the main group exposed to ≥50 mSv vs internal control group (exposed to <50 mSv), affective disorders were present, respectively, in 89 (56.4%) vs 7 (19.1%) (P<0.001), and stress-related disorders in 98 (62.8%) vs 17 (40.4%) (P=0.009). Relative risks (RR) and 95% confidential intervals (95%CI) of Incidence of some neuropsychiatric disorders in liquidators of 1986–1987 related to internal control (doses <50 mSv) were as follows: organic psychosis (RR=3.15; 95% CI: 2.6; 3.7); non-psychotic organic brain damage (RR=1.99; 95% CI: 1.6; 2.5); acute (RR=1.40, 95% CI: 1.3; 1.5), and chronic cerebrovascular disorders (RR=1.23; 95% CI 1.0;1.5). Neuropsychiatric diseases shows a strong, increasing, and approximately quadratic statistically significant (Pv<0.001) relationship with individual dose, yielding an estimated excess relative risk ERR=2.76 Sv-2 (95% CI 1.06–7.15). Conclusions: Liquidators have an excess of cognitive, affective and stress-related disorders. The risk of diseases rises with radiation dose. Radiation risks evealed for organic psychoses, non-psychotic organic brain damage, acute and chronic cerebrovascular pathology.